A Novel Device for Measuring Forces in Endoluminal Procedures. (27th August 2015) - Ranzani, Tommaso; Ciuti, Gastone; Tortora, Giuseppe; Arezzo, Alberto; Arolfo, Simone; Morino, Mario; Menciassi, Arianna
In this paper a simple but effective measuring system for endoluminal procedures is presented. The device allows measuring forces during the endoluminal manipulation of tissues with a standard surgical instrument for laparoscopic procedures. The force measurement is performed by recording both the forces applied directly by the surgeon at the instrument handle and the reaction forces on the access port. The measuring system was used to measure the forces necessary for appropriate surgical manipulation of tissues during transanal endoscopic microsurgery (TEM). Ex-vivo and in-vivo measurements were performed, reported and discussed. The obtained data can be used for developing and appropriately dimensioning novel dedicated instrumentation for TEM procedures.